Managing Global Student Migration in the Twentieth Century
XVII, 292 p. 3 illus.
Keywords: This open-access book examines student migration in the twentieth century, focusing on the Cité Internationale Universitaire de Paris. Established in 1925 by the French government with support from a diverse coalition of international public and private actors, this campus was intended to host up to 10,000 students from various national backgrounds each year, thereby fostering French influence and promoting cross-cultural understanding. In this context, the book traces these students’ trajectories through major social and political movements of the century—such as anti-colonialism, communism, and feminism—from the interwar period to the globalization in the 2000s. It explores the varied backgrounds of students, including democratic elites, exiles fleeing military dictatorships, and students from developing nations. Through this analysis, the book illuminates the forces driving global student mobility and academic diplomacy, assessing the roles of governments, universities, and philanthropic organizations in shaping these efforts. Furthermore, it reveals the complex intersections of class, gender, and race within migrant student communities, for whom the Cité served as a nexus of exchange and cultural transfer. By using the Cité Internationale as a case study, this work offers a distinctive perspective on the global history of student mobility and transnational higher education. Dzovinar Kévonian is a professor of Contemporary History at the University of Caen-Normandy in France, a member of EA Histoire-Territoire-Mémoire, and an associate member of the Institute of Social Sciences of Politics (UMR 7220). Her research focuses on transnational legal, social, and humanitarian issues, itineraries, and practices of actors operating within international and non-governmental organisations on refugee, minority, and human rights issues. Guillaume Tronchet is a senior civil servant at the French Ministry of Higher Education and Research, holding a PhD in History from the University of Paris 1 Panthéon-Sorbonne. A specialist in the history of international academic relations, he is also a research associate at the Institut d’histoire moderne et contemporaine (ENS-PSL, Paris 1, CNRS) and previously directed the GlobalYouth research program at the École Normale Supérieure in Paris.